A multicenter study of the safety and effectiveness of mechanical thrombectomy for patients with acute ischemic stroke not meeting top-tier evidence criteria. (31st January 2017) - Goyal, Nitin; Tsivgoulis, Georgios; Frei, Donald; Turk, Aquilla; Baxter, Blaise; Froehler, Michael T; Mocco, J; Vachhani, Jay; Hoit, Daniel; Elijovich, Lucas; Loy, David; Turner, Raymond D; et al.
Abstract : Background: While mechanical thrombectomy (MT) has become the standard of care for patients with acute ischemic stroke (AIS) with emergent large-vessel occlusions (ELVO), recently published guidelines appropriately award top-tier evidence to the same selective criteria that were employed in completed clinical trials. We sought to evaluate the safety and effectiveness of MT in patients with AIS with ELVO who do not meet top-tier evidence criteria (TTEC). Methods: We conducted an observational study on consecutive patients with AIS with ELVO who underwent MT at six high-volume endovascular centers. Standard safety outcomes (3-month mortality, symptomatic intracranial hemorrhage) and effectiveness outcomes (3-month functional independence: modified Rankin Scale scores of 0–2) were compared between patients meeting and failing TTEC. Results: The sample consisted of 349 (60%) controls fulfilling TTEC and 234 (40%) non-TTEC patients. Control patients meeting TTEC for MT tended to have higher functional independence rates at 3 months (47% vs 39%; p=0.055), while the rates of symptomatic intracerebral hemorrhage (sICH) were similar (9%) in both groups (p=0.983). In multivariable logistic regression models, adherence to TTEC for MT was not independently related to any safety outcome (sICH: OR 0.71, 95% CI 0.30 to 1.68, p=0.434; 3-month mortality: OR 1.27, 95% CI 0.69 to 2.33, p=0.448) or effectiveness outcome (3-month functional independence: OR 0.81, 95% CI 0.48 to 1.37, p=0.434; 3-month functional improvement: OR 0.73, 95% CI 0.48 to 1.11, p=0.138) after adjusting for potential confounders. Conclusions: Approximately 40% of patients with AIS with ELVO offered MT do not fulfill TTEC for MT. Patients who did not meet TTEC had high rates of good clinical outcome and low complication rates.